Architectural Forensics: establishing a date for the construction of Pavitt Cottage, Robinson's Bay, Bank's Peninsula - Cottrell, William (Architectural History Aotearoa, 2012)
Many early New Zealand properties and indeed colonial-made artefacts often lack detailed documentation, provenance and in some cases, any known or relevant history. It is possible to establish new information by analysing the wide range of materials used to build even a modest cottage. Further, it is possible to establish a likely time-frame of construction by looking at improvements in the manufacturing of various imported components. Already known facts can be incorporated with newly-recovered information to provide a broader historic picture. As with archaeology, one object can be used comparatively to determine likely probabilities from other sites. Pavitt Cottage, at Robinson's Bay on Bank's Peninsula was built sometime between 1857 and 1862 with additions in 1865. Local records have been unable to provide a more accurate date. Within the last 15 years it has been "restored" with the potential loss of some useful evidence. This paper will illustrate how it is possible to glean new knowledge from the materials used to try to establish a precise date of construction.